من أعلام الفكر الإسلامي الشيخ أبو اليقظان الصحفي المصلح - بوسعيد, سومية (جامعة الوادي - University of Eloued, 2022)
من أعلام الفكر الإسلامي الشيخ أبو اليقظان الصحفي المصلح الدكتورة :بوسعيد سومية .جامعة جيلالي ليابس .سيدي بلعباس ملخص : الشّيخ إبراهيم بن عيسى أبو اليقظان ( 1888 – 1973م ) شخصيّة إسلاميّة كبيرة، قدّمت للإسلام والمسلمين، عصارة فكر، وخلاصة تجربة، عالج من خلال ذلك أوضاع المسلمين، وحلّل واقعهم، وقدّم لهم الحلول المناسبة، نظم الشعر، وكتب و نشر المقالات في مجالات الإصلاح وألّف الكتب، واشتغل في التعليم. نشط في النّوادي، شارك في جمعيّة العلماء المسلمين الجزائريين، وانضمّ إلى الهيئة. اشترك في الوعظ، وانفرد بالتّوعية. تحرّك في أكثر من صعيد، ونشط مع القريب والبعيد، جاهد بالكلمة، وناضل بالحكمة... ترك للأمّة الإسلاميّة تراثا عظيما غنيّا ،وفكرا عميقا ثريّا يعد الشيخ أبو اليقظان أبو الصحافة الإصلاحية من المساهمين في الحركة الإصلاحية الوطنية والعربية، ممن قل ذكرهم على غرار المصلحين الذي برزوا وركزت عليهم الأبحاث والدراسات، فحريٌ بتلاميذ الشيخ أبي اليقظان وطلبة العلم والباحثين أن يعملوا على نشر أعماله المخطوطة وإخراجها إلى الوجود ليستفيد منها كل مسلم، ففيها العلم الغزير والتجربة الواسعة، والمواقف الإسلامية الشجاعة ، والإخلاص في النية والعمل، والأمل العريض في استعادة الإسلام مجده والمسلمين كرامتهم وعزتهم ،لأننا بعد معرفتنا لما تركه من مؤلفات مطبوعة أو مخطوطة ، وإطلاعنا على ما كتب عنه وهو قليل جدا ، أنه كان في الحقيقة داعية كبيرا سعى لإصلاح المجتمع لإنقاذ المسلمين مما هم فيه من زيغ وضلال في الدين وفساد في الأخلاق . فإن صحافة أبي اليقظان التي تغطي فترة ما بين الحربين العالميتين ( 1926- 1938 ) تعد من أهم المصادر التي لا يمكن للباحث الجاد أن يستغنى عنها ، ففي طيياتها شهادة حية لفترة هي من أغنى فترات تاريخنا صمودا ومقاومة وحصيلتها مادة غنية متنوعة عن الحياة الجزائرية في جميع مجالاتها الإنسانية دينا ، واجتماعيا ، وثقافة ، وسياسة ، واقتصادا .Sheikh Ibrahim bin Issa Abu al-yakdan (1888 – 1973) A large Islamic figure, presented to Islam and Muslims, addressed through the Muslim situation, analyzed their reality, gave them the appropriate solutions, hair systems, wrote and published articles in reform areas and a book, and worked in Education. Active in clubs, participated in the Association of Algerian oulema Muslim , and joined the Commission. Join in preaching, and alone with awareness. Move in more than one level, active with the near and the distant, labored by the word, and struggled wisely... He left the Islamic a great rich heritage, and a deep, rich thought Sheikh Abu alyakdan, the reformist Press, is a contributor to the national and Arab Reformist Movement, who have been said to have been like reformers who have emerged research and studies have focused on them, and students of Shaykh Abual-yakdan, students of science and researchers should work on publishing and taking out the manuscript To exist to benefit every Muslim, who has abundant knowledge, vast experience, courageous Islamic attitudes, sincerity in intention and action, and the broad hope of the restoration of the glory of Islam and of the Muslims their dignity , because after our knowledge of what he left of the writings or manuscript, we were informed of what he wrote about It is very little, that it was really a great advocate for the reformation of society to save Muslims from their astray in religion and corruption in morality. My father's press, which covers the period between the two World Wars (1926-1938), is one of the most important sources that a serious scholar cannot dispense with, it is a living testimony for a period that is one of the richest periods of our history and resistance and its outcome is a rich variety of Algerian life in all its fields now, socially, culture, politics, economics.
مقال
Keywords: الشيخ أبو اليقظان ؛ الفكر الإسلامي ؛ الإصلاح ؛ الصحافة ؛ جمعية العلماء المسلمين الجزائريين; Abou Al-Waqzan ; la presse; réforme; la colonisation